1985
DOI: 10.1007/bf00280887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucagon antibodies on plasma glucose, insulin and somatostatin in the fasting and fed rat

Abstract: A potent high-titre glucagon antibody pool was used to induce a state of acute glucagon deficiency in order to investigate the importance of glucagon in maintaining euglycaemia in the fed and fasted anaesthetised rat. Binding characteristics of the antiserum and evidence of its neutralisation of the biological effects of exogenous glucagon are described. The amount of antibody administered was capable of neutralising up to 12 times the total content of glucagon (approximately 1 nmol) in the rat pancreas. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Concentrations of free glucagon after Glu-mAb treatment were not measured in this study, but results from similar experiments with polyclonal glucagon antisera containing mixtures of clones with equal or lower affinities than Glu-mAb indicate that the plasma concentration of free and thereby active glucagon should be very low [28]. In agreement with our assumption that most of the endogenous glucagon was efficiently neutralized by Glu-mAb we found that immunoneutralization of exogenous glucagon caused blood glucose levels to fall below the initial value, a result which could not be demonstrated in similar experiments with polyclonal antisera [28,39,40].…”
Section: Discussionsupporting
confidence: 84%
“…Concentrations of free glucagon after Glu-mAb treatment were not measured in this study, but results from similar experiments with polyclonal glucagon antisera containing mixtures of clones with equal or lower affinities than Glu-mAb indicate that the plasma concentration of free and thereby active glucagon should be very low [28]. In agreement with our assumption that most of the endogenous glucagon was efficiently neutralized by Glu-mAb we found that immunoneutralization of exogenous glucagon caused blood glucose levels to fall below the initial value, a result which could not be demonstrated in similar experiments with polyclonal antisera [28,39,40].…”
Section: Discussionsupporting
confidence: 84%
“…Conversely, there is ample evidence demonstrating that inhibition of glucagon signaling in vivo leads to a reduction in plasma glucose, or hypoglycemia. It was shown that administration of polyclonal glucagon-neutralizing antibodies abolished the hyperglycemic response to exogenous glucagon in animals (83). A similar observation was made using a high-affinity monoclonal anti-glucagon antibody (11).…”
Section: Glucagon Is a Key Regulator Of Glucose Homeostasis In Vivomentioning
confidence: 53%
“…Insulin-binding reagent was obtained from Wellcome Research Laboratories, Beckenham, Kent; intra-and interassay variations were 133 and 146% respectively. Pancreatic glucagon concentrations were also estimated on large plasma samples by radioimmunoassay as previously described (Tan, Tsiolakis & Marks, 1985). Glucagon antiserum was obtained from Guildhay Antisera, Guildford, Surrey; intra-and interassay variations were 7-3 and 15-2 % respectively.…”
Section: Discussionmentioning
confidence: 99%